Design of an interactive earphone simulator and results from a perceptual experiment - Lindborg, PerMagnus (2015)
The article outlines a psychoacoustically founded method to describe the acoustic performance of earphones in two dimensions, Spectral Shape and Stereo Image Coherence. In a test set of 14 typical earphones, these dimensions explained 66.2% of total variability in 11 acoustic features based on Bark band energy distribution. We designed an interactive Earphone Simulator software that allows smooth interpolation between measured earphones, and employed it in a controlled experiment (N=30). Results showed that the preferred ‘virtual earphone’ sound was different between two test conditions, silence and commuter noise, both in terms of gain level and spectral shape. We discuss possible development of the simulator design for use in perceptual research as well as in commercial applications.